2017
DOI: 10.1007/s40744-017-0077-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effectiveness of Adalimumab in Patients with Rheumatoid Arthritis: An Observational Analysis from the Corrona Rheumatoid Arthritis Registry

Abstract: Introduction Current recommendations for the management of rheumatoid arthritis (RA) focus on a treat-to-target approach with the objective of maximizing long-term health-related quality-of-life in patients with RA. Published studies from randomized clinical trials have reported limited data regarding the long-term efficacy and safety of adalimumab in patients with RA. This study aims to evaluate the long-term (10+ years) persistency and effectiveness of adalimumab in patients with RA in a real-wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…28 Improvements in morning stiffness have previously been observed in patients treated with adalimumab (from the Corrona registry) and etanercept or infliximab compared with patients not receiving anti-TNF treatment, which complement the findings of the present study. 29,30 No new safety signals were identified and the incidence of CZP-related TEAEs were in line with the known safety profile of CZP. 5,6 The limitations of the study included the use of DAS28(CRP) as the preferred measure for the primary outcome as this was not validated in the most recent European League Against Rheumatism (EULAR) recommendations for the management of RA.…”
Section: Safetymentioning
confidence: 71%
See 1 more Smart Citation
“…28 Improvements in morning stiffness have previously been observed in patients treated with adalimumab (from the Corrona registry) and etanercept or infliximab compared with patients not receiving anti-TNF treatment, which complement the findings of the present study. 29,30 No new safety signals were identified and the incidence of CZP-related TEAEs were in line with the known safety profile of CZP. 5,6 The limitations of the study included the use of DAS28(CRP) as the preferred measure for the primary outcome as this was not validated in the most recent European League Against Rheumatism (EULAR) recommendations for the management of RA.…”
Section: Safetymentioning
confidence: 71%
“…28 Improvements in morning stiffness have previously been observed in patients treated with adalimumab (from the Corrona registry) and etanercept or infliximab compared with patients not receiving anti-TNF treatment, which complement the findings of the present study. 29,30…”
Section: Discussionmentioning
confidence: 99%
“…Adalimumab reference product (RP; Humira, AbbVie Ltd, Maidenhead, UK), a fully human monoclonal antibody, has received regulatory approval for RA and several other diseases including psoriatic arthritis, inflammatory bowel disease, plaque psoriasis, axial spondyloarthritis, uveitis, and hidradenitis suppurativa [10,11]. The benefits of adalimumab have been well established in long-term trials and large registries such as the Corrona registry [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Registry study data can be used to examine whether longer-term exposure to a biologic maintains the benefits for reduced disease activity and function impairment. Previous analyses of registry data have shown that RA patients who respond to biologic therapy in the first 6-12 months usually experience persistent benefits if they continue biologic therapy for several years [15][16][17][18][19][20][21][22][23][24]. The objective of this analysis was to examine the effect of cumulative exposure to biologics on patient outcomes over time, as well as predictors for improvement in outcomes.…”
Section: Introductionmentioning
confidence: 99%